The impact of noise for the nursing workers health and the work process - Elias Barbosa Oliveira; Marcia Tereza Luz Lisboa (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Descriptive study with qualitative approach designed to analyse the impact of environment noise on the nursing staff and on work process. Twenty-five members of nursing staff of an intensive therapy center at a university hospital in Niteroi (RJ). participated in the study. For data collection, semi-structured interview was used. Data were analyzed by means of content analysis. As results the workers referred as main source of noise the lack of preventive maintenance of the machines and skills do deal with them. They reported that the noise disturbed, stressed them and led to mistakes and accidents. Therefore, preventive actions and changes need to be implemented by the organization so that it could improve the work environment. Nursing staff members have an important role in helping the organization managers to set a healthier work environment.